Looking beyond the obvious: diagnosis and management of malaria and human immunodeficiency virus coinfection - Anusha M,; Smitha Bhat, (Indian Journal of Case Reports, 2021)
An atypical presentation of malaria with an unusual complication can initially leads to an incorrect diagnosis, whose puzzling clinical features resolves once the correct diagnosis is made and the treatment is initiated. Here, we report one such unusual presentation of vivax malaria which masqueraded as an acute coronary syndrome (ACS) in a 46-year-old male. The patient had been on Tenofovir + Lamivudine+ Efavirenz for acquired immunodeficiency syndrome and presented to us with a history of chest pain, breathlessness, and pedal edema. We found him to have elevated blood pressure, diffuse abdominal tenderness, splenomegaly, and pedal edema. ACS was diagnosed based on the clinical and laboratory features, though the absence of regional wall motion abnormality on the echocardiogram was puzzling. Antiplatelet therapy and statins were started. Although the clinical picture was not typical, the combination of hepatic and renal dysfunction and thrombocytopenia prompted us to test for malaria, which turned out to be strongly positive. The patient received treatment for malaria, after which both clinical and laboratory parameters improved. We present this case to illustrate the diagnostic challenge when coexisting diseases result in atypical presentations of common illnesses.